Application of SWAT Model for Assessing Water Availability in Surma River Basin - Syeda Zehan Farzana; Md. Abu Zafor; Jabed Al Shahariar (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Water discharge is a significant hydrological parameter because it defines the shape, size and course of the stream. This study was initiated to evaluate the performance and applicability of the physically based SWAT model in analyzing the influence of hydrologic parameters on the streamflow variability and estimation of water balance components at the outlet of Kanaighat streamflow station (SW266) of Surma basin. A 30-m resolution digital elevation model (DEM) has been used to delineate catchment boundary. Land use map obtained from global source GLOBCOVER (Europe Space Agency) has been reclassified to match the SWAT land classes. The model was first calibrated for the period from 2003 to 2008 and then validated for the period from 2009 to 2013 using the observed monthly discharge data. Statistical model performance measures, coefficient of determination (R2) of 0.780, the Nash–Sutcliffe Index (NSI) of 0.47 and Percent bias (PBIAS) of -53.5%, for calibration and 0.878, 0.74 and -31.7%, respectively for validation, indicated good performance of the model simulation on monthly time step. The results showed that SWAT can simulate the hydrologic characteristics of the watershed very well.